An Empirical Evidence of Corporate Social Responsibility by Banking Sector based on Bangladesh - Ferdous, Mahjabeen; Moniruzzaman, Md. (Asian Business Review, 2013)
This paper present the current Corporate Social Responsibility practices by banking sector in Bangladesh. It also attempts to examine the importance of CSR (Gaining Competitive advantage, Customer’s and Employee’s Positive Behavior, Financial performance, etc) using open end questionnaire aims to collect respondent’s opinion. Data analyzed by Statistical tool hypotheses (Z statistic-Proportion Test) along with descriptive analysis. DBBL is one of the top most banks in practicing CSR activities. The most practiced area is Education; PCB may diversify CSR practices in women empowerment, poverty alleviation as it is not enough to contribute the overall development of the country as well as other sector such as telecommunication, manufacturing industry may come forward for CSR practices. JEL Classification Code: M14